PENGARUH PENAMBAHAN Sr ATAU TiB TERHADAP STRUKTUR MIKRO DAN FLUIDITAS PADA PADUAN Al-6%Si-0,7%Fe - Suherman Suherman (Jurnal Dinamis, 2009)
AbstractThe aim of work is to study influence of Sr or TiB addition to the microstructure and fluidity of Al-6%Si-0,7%Fe alloys on sand casting process. Al-6%Si-0,7%Fe were melted in crucible furnace at 7300 C and added Sr or TiB. The fluidity of the molten metals were being measured by Birmingham method. The microstructure changes were studied by optical microscope. The results show that the addition of Sr in Al-6%Si-0,7%Fe alloy modify the morphology of the eutectic silicon phase from a coarse platelike structure to fine fibrous structure. The additional of TiB in Al-6%Si-0,7%Fe alloys result fine fibrous structure. The Addition Sr or TiB in Al-6%Si-0.7%Fe alloys decreases fluidity of the molten metals.Keywords: Al-Si; Fluidity; Grain refiner TiB; Modification Sr